From Animal Poisons and Venoms to Medicines: Achievements, Challenges and Perspectives in Drug Discovery - Bordon, Karla de Castro Figueiredo; Cologna, Camila Takeno; Fornari-Baldo, Elisa Corrêa; Pinheiro-Júnior, Ernesto Lopes; Cerni, Felipe Augusto; Amorim, Fernanda Gobbi; Anjolette, Fernando Antonio Pino; Cordeiro, Francielle Almeida; Wiezel, Gisele Adriano; Cardoso, Iara Aimê; Ferreira, Isabela Gobbo; Oliveira, Isadora Sousa de; et al. (Frontiers in Pharmacology, 2020)
Animal poisons and venoms are comprised of different classes of molecules displaying wide-ranging pharmacological activities. This review aims to provide an in-depth view of toxin-based compounds from terrestrial and marine organisms used as diagnostic tools, experimental molecules to validate postulated therapeutic targets, drug libraries, prototypes for the design of drugs, cosmeceuticals and therapeutic agents. However, making these molecules applicable requires extensive preclinical trials, with some applications also demanding clinical trials, in order to validate their molecular target, mechanism of action, effective dose, potential adverse effects, as well as other fundamental parameters. Here we go through the pitfalls for a toxin-based potential therapeutic drug to become eligible for clinical trials and marketing. The manuscript also presents an overview of the current picture for several molecules from different animal venoms and poisons (such as those from amphibians, cone snails, hymenopterans, scorpions, sea anemones, snakes, spiders, tetraodontiformes, bats and shrews) that have been used in clinical trials. Advances and perspectives on the therapeutic potential of molecules from other underexploited animals, such as caterpillars and ticks, are also reported. The challenges faced during the lengthy and costly preclinical and clinical studies and how to overcome these hindrances are also discussed for that drug candidates going to the bedside. It covers most of the drugs developed using toxins, the molecules that have failed and those that are currently in clinical trials. The article presents a detailed overview of toxins that have been used as therapeutic agents, including their discovery, formulation, dosage, indications, main adverse effects and pregnancy and breastfeeding prescription warnings. Toxins in diagnosis, as well as cosmeceuticals and atypical therapies (bee venom and leech therapies) are also reported. The level of cumulative and detailed information provided in this review may help pharmacists, physicians, biotechnologists, pharmacologists and scientists interested in toxinology, drug discovery and development of toxin-based products.